Two-dimensional thermoluminescence dosimetry system for proton beam quality assurance. (July 2016) - Gajewski, J.; Kłosowski, M.; Olko, P.
Abstract: The response of a large-area two-dimensional (2D) thermoluminescence (TL) dosimetry system with 20 × 20 cm 2  TL LiF:Mg, Cu, P foils, developed at the Institute of Nuclear Physics PAN was studied for doses of therapeutic proton beams with energies of 80 MeV, 150 MeV and 225 MeV. The one-hit detector model fitted to measured dose response yielded characteristic doses of 227 Gy, 209 Gy and 203 Gy respectively. The system was applied to investigate geometrical parameters of spots produced by proton pencil beams at the Bronowice Cyclotron Centre IFJ PAN. Mean spot sizes measured with TL foils were compared with mean spot sizes calculated for Gafchromic ® films. It was shown that the 2D TL system was capable to measure the spot size up to peak doses of 20 Gy without additional correction for dose response. For measurements of the spot size using Gafchromic ® EBT3 films an additional calibration must be applied to correct for the non-linear response for doses exceeding 1 Gy. Highlights: Three proton energies were considered: 80, 150 and 225 MeV. Characteristic dose of 227 Gy, 209 Gy and 203 Gy was calculated. The linear dose response was found up to 20 Gy. Spot sizes of pencil beam were measured with 2D TL dosimetry system. The results were compared with Gafchromic EBT3 calculation.